Analysis of Main Trends and Development Directions in the Field of Retail Banking Services - Rayimnazarov Salokhiddin Davirbek (Research Parks Publishers, 2022)
this article examines the main trends observed in the field of retail banking services, their nature and impact on transformational processes. In addition, a dynamic analysis of the results of the activity of the